Comparative Effectiveness of Noninvasive and Invasive Ventilation in Critically Ill Patients with Acute Exacerbation of COPD - Stefan, Mihaela S. (Crit Care Med, 2015)
OBJECTIVE: To compare the characteristics and hospital outcomes of patients with an acute exacerbation of chronic obstructive lung disease (COPD) treated in the ICU with initial noninvasive (NIV) or invasive mechanical ventilation (IMV). DESIGN: Retrospective, multicenter cohort studyof prospectively collected data. We used propensity matching to compare the outcomes of patients treated with NIV to those treated with IMV. We also assessed predictors for NIV failure. SETTING: Thirty-eight hospitals participating in the Acute Physiology and Chronic Health Evaluation (APACHE) database from 2008 through 2012. SUBJECTS: A total of 3,520 with a diagnosis of COPD exacerbation including 27.7% who received NIV and 45.5% who received IMV. MEASUREMENTS AND MAIN RESULTS: NIV failure was recorded in 13.7% from patients ventilated noninvasively. Hospital mortality was 7.4% for patients treated with NIV; 16.1% for those treated with IMV; and 22.5% for those who failed NIV. In the propensity matched analysis, patients initially treated with NIV had a 41% lower risk of death compared with those treated with IMV (RR: 0.59, 95% CI 0.36, 0.97). Factors that were independently associated with NIV failure were SAPS-II score (relative risk = 1.04 per point increase, 95% CI: 1.03, 1.04) and the presence of cancer (2.29, 95% CI: 0.96, 5.45). CONCLUSIONS: Among critically ill adults with COPD exacerbation, the receipt of NIV was associated with a lower risk of in-hospital mortality compared to IMV; NIV failure was associated with the worst outcomes. These results support the use NIV as a first line therapy in appropriately selected critically ill patients with COPD while also highlighting the risks associated with NIV failure and the need to be cautious in the face of severe disease.